Safety effect of terapy with liraglutide, metformin and statins on HBA1C and lipid markers (ApoA1 and ApoB) in patients with T2DM - Penshovska Nikolova, Vera; Nikolov, Hristijan (My University, 2022)
Background; Main hormones involved in regulation of glucose are glucagon like peptid GLP-1 and glucose dependent insulotropic polypeptide GIP. Both of them are inactivated by the enzyme dipeptil peptidasa -4 (DPP-4). Incretin based therapies include GLP -1 receptor agonist and DPP-4 inhibitors which main actions are to increase secretion of insulin and inhibit secretion of glucagon. Apolipoproteins ApoA1 and Apo B are proteins that have role in prediction of cardiovascular disease. Objectives; review of clinical trials show that liraglutide can cause decrease of HbA1c, but the object of our study is that liraglutide combined with statins and metformin can cause safety decreased levels of three examined markers (HbA1C; ApoA1 and ApoB). The aim of study was to examine whether combination of statins with liraglutide and metformin can cause significant decrease in ApoA1, Apo B and Hba1C in patients with DMtip2 and hyperlipidemia. Research and methods; 44 T2DM patients (age=57+-1 year; 47% female; BMI=34,6+-0,9; diabetes duration =7,8+-0,9 year; FPG=185+-8;HbA1C=8,6+-0,1%) were randomized to receive for 16 weeks (i)metformin 2g ; (ii) liraglutide1,8 mg and (iii) statin 20 mg. Statins were given to patients at first visit, while they were on treatment with metformin and GLP before that. ApoA1, Apo B and HbA1c plasma concentration were measured each 4 weeks during the period of 16 weeks. Results; In patients after 4 weeks of treatment with statins, liraglutide and metformin significant reduction in ApoA1, Apo B and HbA1c was registered (p=0,00013, p=0,016 and p<0,0001), compared with basic plasma concentration, measured before beginning of combined treatment. (p=0,02, p=0,00074 and p<0,0001). ApoA1 concentration was increased in 43,6 %patients,16.01% patients, 14.89 % patients and 11,76% patients appropriate in analyzed time spots. After 4 months treatment with statins, Liraglutide and metformin was registered significant decreasing of Apo A1 compared before the treatment. (p=0,00221) Apo B concentration was increased in 62,6 % patients,54.01% patients, 33.89 % patients and 21,76% patients appropriate in analyzed time spots. After 4 months of treatment with statins, liraglutide and metformin was registered significant decreasing of Apo B compared before the treatment (p=0,003). HbA1c concentration was increased in 88,6 %patients,16.01 %patients, 8.89 % patients and 7,76% patients appropriate in analyzed time spots. After 4 months of treatment with statins, liraglutide and metformin was registered significant decreasing of HbA1C concentration compared before the treatment(p<0.0001). Conclusion; These results support a possible role for decreased HbA1C, ApoA1 and ApoB levels in the long term, caused by combined treatment of GLP-1 agonist, metformin and statins which suggest that can be used for prevention of possible cardiovascular future events.
Keywords: Incretin; Apolipoproteins ApoA1; Apo B; HbA1c; cardiovascular